2015
DOI: 10.1038/mi.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids induce both effector and regulatory T cells by suppression of histone deacetylases and regulation of the mTOR–S6K pathway

Abstract: Microbial metabolites such as short chain fatty acids (SCFAs) are highly produced in the intestine and potentially regulate the immune system. We studied the function of SCFAs in regulation of T cell differentiation into effector and regulatory T cells. We report that SCFAs can directly promote T cell differentiation into T cells producing IL-17, IFN-γ, and/or IL-10 depending on cytokine milieu. This effect of SCFAs on T cells is independent of GPR41- or GPR43 but dependent on direct histone deacetylase (HDAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
799
4
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 920 publications
(825 citation statements)
references
References 48 publications
17
799
4
5
Order By: Relevance
“…As SCFA propionate also binds GPR43, even at a low affinity, we are actively investigating whether it also promotes intestinal IgA responses. Although it has been shown that SCFA inhibit histone deacetylases in a GPR41-and GPR43-independent manner, a recent report also suggested that HDAC activity could be regulated in a GPR43-dependent manner 20,46 . We are still unclear at this point as to whether HDAC inhibitory activity of acetate is involved in the regulation of the intestinal IgA responses.…”
Section: Discussionmentioning
confidence: 99%
“…As SCFA propionate also binds GPR43, even at a low affinity, we are actively investigating whether it also promotes intestinal IgA responses. Although it has been shown that SCFA inhibit histone deacetylases in a GPR41-and GPR43-independent manner, a recent report also suggested that HDAC activity could be regulated in a GPR43-dependent manner 20,46 . We are still unclear at this point as to whether HDAC inhibitory activity of acetate is involved in the regulation of the intestinal IgA responses.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this idea, lineage-specific cytokine-encoding genes that affect T cell differentiation undergo dynamic changes in microenvironmental factors influence T cell function will provide further insight into immune cell biology and could lead to new approaches to treating human diseases. produced by bacteria induce differentiation of colonic T reg cells (Furusawa et al, 2013;Smith et al, 2013) and also Th17 cells under certain conditions (Park et al, 2015). The vitamin A metabolite retinoic acid can synergize with TGF- to stimulate T reg conversion (Coombes et al, 2007;Denning et al, 2007;Mucida et al, 2007;Sun et al, 2007;Elias et al, 2008).…”
Section: Emerging Topics and Concluding Remarksmentioning
confidence: 99%
“…Microbial co-metabolism can affect T-cell signaling pathways by production of amino-acids, fatty acids and butyrate especially production of proinflammatory Th17 and anti-inflammatory Tregs [10][11]. This co-metabolism can determine the result of immunotherapeutics and cancer cell survival [12][13][14].…”
Section: Antibiotic Effect On Gut Microbiota and Immunotherapeutic Efmentioning
confidence: 99%